Actinic keratosis – diagnostic and therapeutic recommendations of the Polish Dermatological Society - Reich, Adam; Lesiak, Aleksandra; Narbutt, Joanna; Owczarczyk-Saczonek, Agnieszka; Pastuszczak, Maciej; Sobjanek, Michał; Szepietowski, Jacek; Walecka, Irena; Owczarek, Witold (Dermatology Review/Przegląd Dermatologiczny, 2024)
Actinic keratosis is a common skin condition that has the potential to develop into malignant neoplastic lesions. Factors that are known to increase the likelihood of developing actinic keratosis include older age, male gender, UV exposure, and immunosuppressive treatment. Understanding the pathogenesis and significance of actinic keratosis as an initial form of the neoplastic process associated with a sequence of lesions arising on photodamaged skin has led to the concept of field cancerization. The choice of the optimal therapeutic pathway depends on the number of actinic keratosis lesions and the degree of photodamage in the skin, as well as the advancement of skin lesions. The clinical presentation of skin lesions also allows monitoring of the patient’s condition over time and assessing response to treatment, and facilitates rational decisions regarding potential therapy adjustments. This article outlines the guidelines for the diagnosis and treatment of actinic keratosis in Poland and presents an evidence-based management regimen that incorporates the practical clinical experience of dermatology experts. The recommendations cover a range of topics including topical treatment options, cryosurgery, photodynamic therapy with a photosensitizing agent, and combination treatments.